Stem Cells in Domestic Animals: Applications in Health and Production - Iacono, Eleonora; Merlo, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Stem cells are an attractive tool for cell-based therapies in regenerative medicine, both for humans and animals. The research and review articles published in this first book of the Collection "Stem Cells in Domestic Animals: Applications in Health and Production" are excellent examples of the recent advances made in the field of stem/stromal cell research in veterinary medicine. In this field, sophisticated and new treatments are now required for improving patients' quality of life; in livestock animals, the goal of regenerative medicine is to improve not only animal welfare but also the quality of production, aiming to preserve human health. The contributions collected in this book concern both laboratory research and clinical applications of mesenchymal stem/stromal cells. The increasing knowledge of cell-based therapies may constitute an opportunity for researchers, veterinary practitioners, and animal owners to contribute to animal and human health and well-being.